Strategi Pengembangan Produk Paket Wisata (Studi Kasus di PT. Viva Wisata Indonesia) - R. Anggi P. Supriadi (Politeknik Pariwisata NHI Bandung, 2022)
Business competition in the travel industry is increasingly sharp and fierce. The role of conventional travel agents began to be replaced by online travel agents through various products supported by an application. But not all travel company products are controlled by online travel agents, likes tour package products. The purpose of this research is to produce a tour package product development strategy that can be used by PT. Viva Wisata Indonesia, as well as conventional travel agents in general, in the face of competition problems, especially facing online travel agents. Not all products in the travel industry can be serviced according to the technology sistem, such as tour package products, there are many factors that cause these products to require touch and communication between humans. Tour package products which consist of various components of tour packages, in the preparation and planning require continuous communication to get the necessary details so that the packages produced are in accordance with the needs of consumers. The suggestions that can be given from this research are related to strategies in developing tourism package products in order to remain competitive in the future, such as market expansion so that the products produced are more varied, making product variations between ready packages and tailor-made, and the formation of creative teams related to the preparation of tour packages that are in accordance with the current trends.